2008
DOI: 10.1111/j.1365-2524.2008.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Formal support of stroke survivors and their informal carers in the community: a cohort study

Abstract: This cohort study, aims to explore formal care provision to stroke survivors and their informal carers in the community in the UK. An initial cohort of 105 cohabitant carers of first-time stroke patients was recruited while the stroke patient was in hospital. Structured face-to-face interviews were carried out with carers prior to discharge of the stroke patient home, at 6 weeks after discharge, and 15 months after stroke. Questionnaires included measures of psychological health (CIS-R), physical health (self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Nevertheless, the inevitable emotional upheavals were attenuated by the presence and availability of family and friends who provided support or who encouraged caregivers to get help for themselves or for the person they cared for [34]. It has been demonstrated that caregivers who profit from social support also need less respite services [35]. Our participants had both a high number of support needs and respite needs, indicating that their family and friends did not or could not provide all of the assistance they needed.…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, the inevitable emotional upheavals were attenuated by the presence and availability of family and friends who provided support or who encouraged caregivers to get help for themselves or for the person they cared for [34]. It has been demonstrated that caregivers who profit from social support also need less respite services [35]. Our participants had both a high number of support needs and respite needs, indicating that their family and friends did not or could not provide all of the assistance they needed.…”
Section: Discussionmentioning
confidence: 80%
“…The interviewer then measured QoL (using the Newcastle Stroke-Specific QoL Measure, newsqol) [7], functional impairments (with American Heart Association Stroke Outcome Classification, AHA.SOC) [30], and dissatisfaction with information and home-care services [31,32]. As Luxembourg is multilingual, the questionnaire was in four official languages.…”
Section: Methodsmentioning
confidence: 99%
“…Dissatisfaction with perceived information and home-care services received was measured for ten issues as shown in Figure 1[31,32]. Information was gathered about community support, coordination and appropriateness of services, characteristics of stroke, speed of change, listening and being heard, problem management and accuracy of information.…”
Section: Methodsmentioning
confidence: 99%
“…Problems and needs of both patients and carers must be identified in order to implement the necessary actions in RHB programs (Simon & Kumar, 2008). Social and family support are crucial to optimizing functional outcome after stroke and achieving a better quality of life for patients (MacKenzie & Chang, 2002;Clarke, Marshall, Black & Colantonio, 2002), mostly with moderate or severe impairment after stroke (Edwards, Hahn, Baum & Dromerick, 2006).…”
Section: Introductionmentioning
confidence: 99%